Silica Sand as an Alternative Source of Renewable Energy within the Green Economy Concept: A Maqasid al-Shari'ah Perspective - Miftahul Hasanah; Sumayyah Nurhafizhah; Elvi Wahyulianti (Mauriduna : Journal of Islamic Studies, 2026)
The concept of the Green Economy emerges to address the negative impacts of pollution and environmental damage caused by increasing economic activities. One of the programs of the Green Economy is Renewable Energy, which sources its energy from nature. A potential source of Renewable Energy, especially in Indonesia, is silica sand. This research uses a qualitative method aimed at analyzing the challenges in integrating silica sand as the main raw material in the production of solar panels as an environmentally friendly alternative energy to fossil fuels. It also outlines the future prospects of the silica sand industry, including its impact on regulations, industrial development, and social aspects, with a review of maqashid sharia, using fiqh bi’ah (environmental jurisprudence). The results of this research are expected to serve as a basis for decision-makers, create jobs, and improve the quality of life for the community. Thus, the researcher can conclude the cohesion and correlation between Green Economy, renewable energy, the silica sand industry, and Maqashid Syariah. The results of this research are expected to serve as a basis for decision-makers, create job opportunities, and improve the quality of life for the community.